Mortality of the Clam Anomalocardia brasiliana Population in the Pirajubaé Marine Extractive Reserve: Effect of Climate Events? - Vaquero, Ronnie Alexandre Moreira; Sühnel, Simone; Cargin Ferreira, Eduardo (Anuário do Instituto de Geociências, 2022)
In February 2015, an event of massive mortality of the clam Anomalocardia brasiliana was reported in the Pirajubaé Marine Extractive Reserve (RESEX), located in Florianópolis, SC. To investigate whether the cause of the event was related to climate and/or environmental factors, daily data of air temperature, precipitation, global solar radiation and lowest day tide from different databases of a 4-month interval (November, December, January, and February) from 2010 (beginning in November of 2010) to 2017 were collected. Based on the analyzed parameters, no changes that could be related to the occurrence of massive mortality of clams in February 2015 were observed. This analysis also indicates that there is no relation between the studied parameters and the absence of recovery of the natural stock of these organisms.